Development of software for healthcare in the context of COVID-19 - Kasylkasova К.; Yessengaliyeva Ж. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2021)
The article analyzes existing devices and apps in the field of health care in the Play Market, contributing to the search for acceptable solutions during the spread of the COVID-19 coronavirus infection. The authors propose a mobile application using Big Data analytics that can assist in a pandemic by providing remote access for online visits to health care organizations. The app includes the tracking of infected users and reports it on a map to alert others, while maintaining complete anonymity for the users themselves. The results of "big data" processing make it possible to retrieve patient data as quickly as possible. The speed at which data can be accessed and processed is an important quality criterion for the technologies that make up Big Data. Access to the application is planned via Google Play.